Intraocular complement activation is related to retinal vascular and neuronal degeneration in myopic retinopathy - Zeng, Ling; Li, Xiaoning; Pan, Wei; Tang, Yao; Lin, Ding; Wang, Min; Cai, Wang; Zhu, Ruiling; Wan, Jianbo; Huang, Linghua; Xu, Heping; Yang, Zhikuan (Frontiers in Cellular Neuroscience, 2023)
To investigate the relationship between the intraocular levels of complement proteins and myopia-related retinal neuronal and vascular degeneration.Methods: Aqueous humour from 147 myopic patients, including 60 low-myopia and 87 high-myopia were collected during Implantable Collamer Lens implantation surgery. All participants received comprehensive ophthalmic examinations, including logMAR best corrected visual acuity, axial length measurement, fundus photography and ocular B-scan ultrasonography. The myopic eyes were further classified into simple myopia (SM, n=78), myopic posterior staphyloma (PS, n=39) and PS with myopic chorioretinal atrophy (PS+CA, n=30). Retinal thickness and vascular density in the macula (6x6mm) and optic nerve head (4.5x4.5mm) were measured using Optical Coherence Tomography (OCT) and OCT angiography (OCTA). The levels of complement proteins including C1q, C3, C3b/iC3b, C4, CFB, CFH, C2, C4b, C5, C5a, CFD, MBL and CFI in the aqueous humour were measured using the Luminex Multiplexing system. The real-time RT-PCR was conducted to examine the expression of complement genes (C1q, C2, C3, C4, CFI and CFD) in the guinea pig model of longterm form deprivation-induced myopic retinal degeneration.Results: OCTA showed that retinal neuronal thickness and vascular density in superficial and deep layers of the macular zone as well as vascular density in the optic nerve head were progressively decreased from SM to PS and PS+CA (p <0.05). The aqueous humour levels of C1q, C3, C3b/iC3b, C4, CFB, CFH, C2, C4b, C5 and CFI were significantly higher in high-myopic eyes compared to those in low-myopic eyes. Further subgroup analysis revealed the highest levels of complement components/fragments in the PS+CA group. The intraocular levels of complement factors particularly C3b/iC3b and C4 were negatively correlated with macular zone deep layer retinal thickness and vascular density and optic nerve head vascular density. The expression of C2, C3 and C4 genes was significantly higher in guinea pig eyes with myopic retinal degeneration compared to control eyes.The intraocular classical pathway and alternative pathway of the complement system are partially activated in pathological myopia. Their activation is related to the degeneration of retinal neurons and the vasculature in the macula and the vasculature in the optic nerve head.